Metaphors and Symbols of Sufism in the Markum Sasak Text: A Semiotic Study - Aswandikari, Sukri, Burhanuddin, Syaiful Musaddat, Johan Mahyudi, Saharudin, Irma Setiawan, Suhaib A (Journal of Educational Studies, 2025)
This study aims to identify the forms of metaphors and symbols and to interpret their Sufi meanings in the Markum Sasak text, Pupuh Sinom stanzas 1–21. The Markum text is a form of Sasak suluk literature that represents the spiritual journey of human beings toward ultimate knowledge and ma‘rifatullah (gnosis of God). This research employs a qualitative descriptive method with a semiotic approach supported by conceptual metaphor theory, hermeneutics, and Sufism studies. The data consist of words, phrases, lines, and stanzas in the Markum text that contain Sufi metaphors and symbols. Data were collected through textual study and note-taking techniques, while data analysis was conducted through metaphor identification, symbol classification, semiotic analysis, hermeneutic interpretation, and Sufi meaning construction. The findings reveal that the Markum text contains metaphors of journey, breath, spiciness, light, and self-surrender. In addition, the text incorporates symbols related to figures, spiritual teachers, place names, nature, animals, mosques, body-space, dhikr, and divine realities. These metaphors and symbols collectively form a system of signs that represents the stages of suluk (spiritual wayfaring), tazkiyat al-nafs (purification of the soul), spiritual etiquette toward teachers, dhikr, fan?’ (self-annihilation), and ma‘rifah (gnostic knowledge of God). Therefore, the Markum text functions not only as a traditional Sasak literary work but also as a culturally grounded medium for Sufi education and spiritual instruction.